UPAYA DINAS KEBUDAYAAN DAN PARIWISATA DENGAN LEMBAGA ADAT MELAYU RIAU KABUPATEN ROKAN HULU DALAM PELESTARIAN BUDAYA DAERAH TAHUN 2015 - Purwanto, Rahmat; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Regional culture is a nation's wealth that needs to be considered and handled seriously, especially in entering regional autonomy and the era of globalization. Believe it or not, the importance of the existence of local culture, because this culture in fact gives a huge contribution to the establishment of national identity, and also for the regeneration of our nation. The inheritance must be maintained so as not to fade or disappear so that it can be studied and preserved by the next generation. Although the culture of each society is not the same, as in Indonesia which consists of different ethnic groups, but every culture has the same characteristics or traits. Therefore it is necessary efforts of the Department of Culture and Tourism with Malay Customary Institutions Riau Rokan Hulu regency in the preservation of regional culture. The purpose of this study is to find out how the efforts of the Department of Culture and Tourism with Malay Customary Institutions Riau Rokan Hulu regency in the preservation of regional culture in 2015. Type of research used is descriptive qualitative research methods. Data collection techniques in this study is to use interviewing techniques and documentation. Based on the results of research can be concluded that the efforts undertaken by the Department of Culture and Tourism with Malay Customary Institutions Riau Rokan Hulu regency in the issue of preservation of local culture has not run optimally. There are internal factors that are internal factors in Malay Customary Institutions Riau Rokan Hulu regency such as not intensive communication and lack of effective coordination. In addition, external factors such as the lack of community participation that hampered efforts to preserve the culture of the region.Keywords: Communication, Coordination, Cultural Conservation, Efforts